Experimental Investigation of Stall Inception Mechanisms of Low Speed Contra Rotating Axial Flow Fan Stage - Tegegn Dejene Toge; A. M. Pradeep (International Journal of Rotating Machinery)
The present paper is an attempt in understanding the stall inception mechanism in a low speed, contra rotating axial flow fan stage, using wavelet transforms. The rotors used in this study have relatively large tip gap (about 3% of the blade span) and aspect ratio of 3. The study was carried out near stall and at stall mass flow conditions for different speed ratios of rotor-2 to rotor-1. Unsteady pressure data from the casing wall mounted sensors are used to understand the stall inception mechanism. The wavelet transform clearly indicates that stall inception occurs mainly through long length scale disturbances for both rotors. It also reveals that short length disturbances occur simultaneously or intermittently in the case of rotor-1. The analysis shows the presence of a strong modal disturbance with 25–80% of the rotor frequency in the case of rotor-1 at the stall mass flow for all the speed combinations studied. The most interesting thing observed in the present study is that the frequency amplitude of the disturbance level is very small for both rotors.